Physical Properties of Five Brands of K-Files - Izadi, Arash; Shahravan, Arash; Shabani Nejad, Hoda (Iranian Endodontic Journal, 2016)
Introduction: Endodontic K-files are major tools for cleaning and shaping of the root canal systems. As there are various K-files available in Iranian market, the physical properties of the five available brands were investigated to assist the clinician when selecting suitable endodontic K-files according to the intended application. Materials and Methods: Physical properties (including debris creation, machinery defect and corrosion) of the selected K-files were investigated by a scanning electron microscope (SEM) under 250× magnification. For evaluating the flutes number, a stereomicroscope was used with 40× magnification. Results: Maximum and minimum debris and corrosion were observed in the Larmrose and Perfect K-files, respectively. Dentsply showed the least machinery defects. Other brands had intermediary properties. In addition, Larmrose K-files showed the maximum flutes number compared to the other brands. Conclusion: According to the results, none of the K-files had the ideal properties. More studies regarding the physical properties of the K-files and their clinical efficacy, are suggested. Keywords: Corrosion; Debris; Physical Properties; Scanning Electron Microscopy